1993
DOI: 10.1080/00288306.1993.9514570
|View full text |Cite
|
Sign up to set email alerts
|

Mafic and ultramafic mantle and deep crustal xenoliths from Banks Peninsula, South Island, New Zealand

Abstract: Mafic and ultramafic xenoliths of spinel lherzolite, wehrlite, websterite, pyroxenite, and metagabbro (mafic granulite) occur in a basanite plug forming Le Bons Bay Peak on the eastern flanks of Akaroa volcano, Banks Peninsula. Spinel lherzolites are assigned to the Cr-diopside xenolith suite and are interpreted to represent fragments of depleted upper mantle derived from a depth of c. 60 km. Pyroxenites belong to the wehrlite series Al-augite xenolith suite and may represent basaltic cumulates derived from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, garnet–orthopyroxene–spinel–sillimanite‐bearing granulite xenoliths occur in Late Cretaceous volcanic rocks at Mt. Somers (Barley, ; Figure inset), and clinopyroxene–orthopyroxene granulite xenoliths occur in Miocene volcanic rocks on Banks Peninsula (Sewell et al., ; Figure inset). There is insufficient published modal and chemical data to accurately calculate the equilibration pressures of these other xenoliths but their occurrences point to granulite likely being widespread in the lower crust of the South Island.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, garnet–orthopyroxene–spinel–sillimanite‐bearing granulite xenoliths occur in Late Cretaceous volcanic rocks at Mt. Somers (Barley, ; Figure inset), and clinopyroxene–orthopyroxene granulite xenoliths occur in Miocene volcanic rocks on Banks Peninsula (Sewell et al., ; Figure inset). There is insufficient published modal and chemical data to accurately calculate the equilibration pressures of these other xenoliths but their occurrences point to granulite likely being widespread in the lower crust of the South Island.…”
Section: Discussionmentioning
confidence: 99%
“…Granulite xenoliths have been found in volcanic rocks erupted through the Eastern Province in the North Island (Graham, 1987;Gruender, Stewart, & Foley, 2010) and South Island (Barley, 1987;Dickey, 1968a;Reay & Sipiera, 1987;Sewell, Hobden, & Weaver, 1993). In situ granulite facies rock occurs in the exhumed lower crust of the Cretaceous arc preserved in Fiordland within the Western Province (Figure 1 inset).…”
Section: Geological Settingmentioning
confidence: 99%
“…Previous investigation of Zealandia peridotitic xenoliths has been at reconnaissance level at best. Brief petrographic descriptions and/or mineral chemistries have been reported by Brown [1954], Wright [1967], Wallace [1975], Price and Wallace [1976], Reay and Sipiera [1987], Brodie and Cooper [1989], Tulloch and Nathan [1990], Sewell et al [1993], Hoke et al [2000], Duclos et al [2005], McCoy-West et al [2013], and Scott et al [2014]. He isotopes were reported for 10 samples [Hoke et al, 2000] and Duclos et al [2005] reported seismic anisotropy measurements on eight of those specimens.…”
Section: Peridotite Characterizationmentioning
confidence: 91%
“…Brief petrographic descriptions and/or mineral chemistries have been reported by Brown [], Wright [], Wallace [], Price and Wallace [], Reay and Sipiera [], Brodie and Cooper [], Tulloch and Nathan [] , Sewell et al . [], Hoke et al . [], Duclos et al .…”
Section: Peridotite Characterizationmentioning
confidence: 99%
“…In the northern half of the island, isolated occurrences are found within the Cookson Volcanics in Marlborough (Reay, 1993) and sporadic dykes in Westland (Tulloch & Nathan, 1990). Further south, mantle xenoliths are more common, having been entrained in a range of small-scale basaltic volcanic edifices, including the Akaoroa Volcano (Sewell et al, 1993;McCoy-West et al, 2013), Deborah Volcanics (Reay et al, 2002), Waipiata Volcanics (Wright, 1966;Price & Green, 1972;Rae, 1990;Reay et al, 1991;Scott et al, 2014a), and Dunedin Volcano (Hoke et al, 2000;Price et al, 2003). Additionally, mantle xenoliths are also observed within the Alpine Dyke Swarm (Wallace, 1975;Cooper et al, 1987;Scott et al, 2014b).…”
Section: Geological Settingmentioning
confidence: 99%